Undergraduate nurses reflections on Whatsapp use in improving primary health care education - Juliana J. Willemse (AOSIS, 2015)
Background: The global use of mobile devices with their connectivity capacity, and integrated with the affordances of social media networks, provides a resource-rich platform for innovative student-directed learning experiences. Objective: The objective of this study was to review the experiences of undergraduate nurses on the improvement of primary health care education at a School of Nursing at a University in the Western Cape, South Africa, through the incorporation of a social media application, WhatsApp. Method: A qualitative, exploratory, descriptive, and contextual design was used to explore and describe data collected from a purposive sample of 21 undergraduate nursing students. The study population was engaged in a WhatsApp discussion group to enhance their integration of theory and clinical practice of the health assessment competency of the Primary Health Care Module. Participants submitted electronic reflections on their experiences in the WhatsApp discussion group via email on completion of the study. Thematic analysis of the qualitative data collected was done according to Tesch's (1990) steps of descriptive data analysis in order to identify the major themes in the study. The electronic reflections were analysed to explore their rich, reflective data. Results: Seven themes were identified that included: positive experiences using the WhatsApp group; the usefulness of WhatsApp for integrating theory and clinical practice; the availability of resources for test preparation; opportunity for clarification; anonymity; exclusion of students as a result of the lack of an appropriate device, and the application caused the battery of the device to run flat quickly. Conclusion: The results of the experiences of students in the WhatsApp discussion group could be used to inform the use of social media applications in teaching and learning, with the purpose of enhancing the integration of the theory and clinical practice.